SUPPLY CHAIN ANALYSIS TO REDUCE DELAYS ON GREEN BUILDING PROJECTS WITH ANALYTICAL HIERARCHY PROCESS METHOD - Rossy Armyn Machfudiyanto; Ammar Syahreza (Jurnal Infrastruktur, 2022)
In developing countries such as Indonesia with high population growth, the need for development is also increasing. However construction is responsible for adverse impacts on the environment ranging from extraction, processing and transportation of raw materials, construction, and operation of building facilities. The building sector is also the largest contributor to energy use (about 40%). Based on this, innovations emerged in the form of Green Buildings to reduce the negative impact on the environment. However, in the implementation of green buildings, obstacles are often found in the form of schedule delays, one of which is caused by activities in the supply chain. This study uses the Analytical Hierarchy Process (AHP) method to identify and analyze activities in the supply chain. It was found that the strategy in reducing delays in green building is supply chain that focuses on efficiency.